Analysis of Driver Position Control on Electronic Power Steering (EPS) Using PID - Suprawikno Suprawikno; Muhammad Haddin; Arief Marwanto (Journal of Telematics and Informatics, 2020)
Abstract This research present about a steering control system on a vehicle whicgh is called Electrical Power Steering (EPS) that aims to observe and compare the position of EPS system with and without using PID controller. The EPS system has a state space order by 6x6 with one of the motor outputs to be controlled by a Proportional-Integral-Derivative (PID) controller and uses the MATLAB application as a simulation of the EPS system. The simulation is carried out in two stages, namely the simulation of an EPS system without controlling and simulating an EPS system using a PID controller. The results show ,that the position controller on EPS with the PID control method reaches the desired position with the parameter value Kp = 500, Ki = 500 and Kd = 200 while the input step is 1. The system output response has an overshoot value closes to 0, a rise time of 0.005 seconds. More over, EPS system which unutilized controllers, the output responseis can not reached the reference value. Keywords—Electric Power Steering (EPS), Proportional-Integral-Derivatif (PID), Simulation.